(untitled) (Confluenţe Bibliologice, 2018)
The MISISQ Project - Modern Information Services for Improvement Study Quality, held in the period 2013-2016, had as applicants European colleagues from the Library of Kaunas University of Medicine, Lithuania, director Meilė Kretavičienė, Scientific Library of Nicolae Testemitanu State University of Medicine- Liubovi Karnaeva, National Coordinator, Director of the Scientific Library, Riga Technical University, Latvia, Hungary - University of Debrecen and Romania - “Iuliu Hatieganu” University of Medicine and Pharmacy in Cluj-Napoca, have ensured an efficient management, a high organizational culture, mobility platforms, training and integration into the international professional community for Moldovan librarians.